Coastal Tourism's Impact on Local Livestock Farming at Bilik Sijile Beach, Baluran National Park - Aprylasari, Dede; Azizah, Siti (Faculty of Animal Science, Universitas Gadjah Mada, 2025)
This research aims to analyze the development of coastal tourism at Sijile Beach and its impact on local beef cattle farming businesses. This research uses a quantitative approach with qualitative data as support, which includes interviews with key informants and surveys of around 40 breeders. The analysis was conducted to understand how tourism development affects livestock farmers' attitudes and identify policies and practices that can improve their welfare. PESTEL analysis identified political, economic, social, technological, environmental, and legal factors influencing Sijile Beach livestock farming. Political factors include conservation policies that limit land access for livestock breeders. In contrast, economic factors indicate challenges and opportunities arising from tourism, including rising land prices and opportunities for economic diversification. Social factors describe changes in cultural values and potential conflict between tourists and local communities. Technological factors indicate a lack of use of technology by livestock farmers, which limits their operational efficiency. Environmental impacts include habitat degradation and pollution due to tourism activities. Legal factors reveal problems in policy implementation and the need for local community participation in decision-making. SWOT analysis highlights strengths, such as solid local resources and a potential market of tourists, as well as weaknesses, such as technological limitations and pressure on natural resources. Opportunities include sustainable tourism development and diversification of the local economy, while threats include the environmental impact of tourism and competition with the tourism sector. These findings demonstrate the need for balanced and inclusive policies to integrate tourism with livestock and the importance of technology training and support for livestock adaptation. This research provides important insights for stakeholders in designing strategies that support ecosystem sustainability and the welfare of local communities